Seismic Analysis of Deep Water Pile Foundation Based on Three-Dimensional Potential-Based Fluid Elements. (11th April 2013) - Wei, Kai; Yuan, Wancheng
Abstract : This paper investigates the use of three-dimensional (3D) ϕ - u potential-based fluid elements for seismic analyses of deep water pile foundation. The mathematical derivations of the potential-based formulations are presented for reference. The potential-based modeling technique is studied and validated through experimental data and analytical solutions. Earthquake time history analyses for a 9-pile foundation in dry and different water environments are conducted, respectively. The seismic responses are discussed to investigate the complex effect of earthquake-induced fluid-structure interaction. Through the analyses, the potential-based fluid and interface elements are shown to perform adequately for the seismic analyses of pile foundation-water systems, and some interesting conclusions and recommendations are drawn.